3D Hierarchical Graphene‐CNT Anode for Sodium‐Ion Batteries: a First‐Principles Assessment. Issue 10 (14th July 2022) - Ma, Jiachen; Yang, Chen; Li, Qiuhui; Liu, Shiqi; Xu, Linqiang; Fang, Shibo; Sun, Xiaotian; Quhe, Ruge; Pan, Feng; Lu, Jing
Abstract: A thermodynamically and kinetically stable 3D hierarchical carbonaceous nanostructure is constructed to examine its potential as an anode for sodium‐ion batteries (SIBs). Heptagonal and quadrilateral staggered carbon rings are formed where the graphite layers and the CNT interconnect vertically. Based on first‐principles calculations, such a graphite‐CNT hybrid with expanded interlayer spacing allows effective binding to Na atoms and contributes a high specific capacity of 324.3 mAh g −1 . It maintains a great electronic conductivity for both pristine and Na‐adsorbed graphite‐CNT along the expanded graphite layers, and constructs a 3D electronic transport network when a large number of Na atoms are adsorbed. This hierarchical nanostructure predicts a fast inner 3D Na‐ion transport network, with energy barriers of 0.56 and 0.50 eV along the expanded graphite layer and the CNT channel, respectively. This research manifests the feasibility of obtaining well‐performed graphite‐based anodes for SIBs through purposeful microcosmic morphology modification. Abstract : The stable 3D hierarchical graphite‐CNT (Gr‐CNT) structure provides 3D transport networks for both Na ions and electrons. A high specific capacity of 324.3 mAh g −1 is predicted.